PENGGUNAAN ARCH BAR PADA FRAKTUR DENTOALVEOLAR - Nicco Marantson (Majalah Biomorfologi, 2019)
Background: Mandibular fracture is the most common case of craniofacial fracture. Nowadays, there are many methods available for treating mandibular fracture, and yet there has been no single method that can be applied to all fracture cases. Open reduction and rigid internal fixation is often used as a choice of treatment, but it needs surgical treatment and higher cost. Objective: To describe an alternative treatment for dentoalveolar fracture. Case: A 22-year-old man with simple mandibular dentoalveolar fracture due to traffic accident 12 days prior to patients’ visit to the dental hospital. Patient also suffered from zygomatic, infraorbital and frontal fractures. Mandibular dentoalveolar fracture was treated by debridement, surgical refracturing and fixation on mandibular teeth using arch bar only. Discussion: Abnormal function that is caused by dentoalveolar and bone destruction needs to be treated by anatomy reduction based on good occlusion. The advantages of non-surgical reposition are no scarring on extra oral features and lower risk of complication. Conclusion: Repositioning and fixation using arch bar without Intermaxillary Fixation (IMF) can be used as an alternative treatment in fixing mandibular fracture.